Clostridia as Promising Biofactory for Heterotrophic (Fructose) and Autotrophic (C1-Gas) Fermentation - Marina Fernández-Delgado; Mónica Coca; Susana Lucas; María Teresa García-Cubero; Juan Carlos López-Linares (Fermentation)
This study compared the performance of Clostridium ljungdahlii and Clostridium aceticum in the fermentation of fructose and C1-gasses (CO, CO2, N2) to produce valuable products such as ethanol and acetic acid. In heterotrophic fermentation (fructose), C. ljungdahlii yielded high ethanol concentrations (350 mg/L) and acetic acid (500 mg/L), with optimal production at pH 8 on the first day of fermentation. Although autotrophic fermentation (C1-gasses) resulted in lower ethanol levels (200 mg/L), it remained a viable option. Conversely, C. aceticum predominantly produced acetic acid in both fermentation modes, with higher concentrations in the heterotrophic fermentation (1600 mg/L) than the autotrophic fermentation (380 mg/L). These findings demonstrate the versatility of both microorganisms for producing valuable metabolites. C. ljungdahlii shows promise for bioethanol production, while C. aceticum excels at generating acetic acid, a crucial component in bioplastics and various industrial processes.